PROBLEM-BASED LEARNING ASSISTED BY SCROLLING PICTURE MEDIA TO IMPROVE THE THIRD-GRADE ELEMENTARY STUDENTS’ SKILLS IN WRITING EXPRESSION - Imroatul Mufidah; Suyono; Radeni Sukma Indra Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the improvement of third-grade elementary students’ writing skills of expression (instruction, announcement, appreciation, and invitation) of grade 3 elementary students by applying a problem-based learning model assisted by Scrolling Picture media. The research method used was classroom action research. The research was conducted in two cycles. Each consists of four stages,namely planning, acting, observing, and reflecting. The results indicate an increasing average of students' skills in writing expressions (instruction, announcement, appreciation, and invitation) in class. An increasing average score of writing expression skills was 71 when the pre-test results increased to 93 in the post-test of cycle I. In this cycle, the average score increased to 22 or 31%. Meanwhile, students who have reached the Minimum Completeness Criteria have also increased from 46% to 89%. In cycle II, otherwise, the student’s skills to write expressions increased compared to the cycle I post-test, which was from 93 in the post-test of cycle I increased to 98 in the post-test of cycle II. In this cycle, the average score increased by 5 or 5.3%. Meanwhile, students who have reached the Minimum Completeness Criteria also increased from 89% to 100%. It is considered satisfying enough for teachers and researchers as the indicator has been achieved successfully. It can be concluded that there is an increasing average value of expression writing skills by applying the problem-based learning model assisted by Scrolling Picture media. The increase is also seen in the students’ enthusiasm and motivation in participating in learning,carrying out responsibility, and conducting cooperation in finishing the tasks provided by the teacher.